Superalloys 718, 625, 706 and Various Derivatives (1997) 1997
DOI: 10.7449/1997/superalloys_1997_47_54
|View full text |Cite
|
Sign up to set email alerts
|

Center Segregation. Freckles and Development Directions for Niobium-Containing Superalloys

Abstract: Macrosegregation defects, such as freckles and center-segregates, are currently one of the main problems encountered by attempts at scaling-up ingot diameters in order to supply industrial gas turbine manufacturers. Focusing on niobium-containing superalloys (IN7 18, IN706 and IN625), interdendritic liquid segregation and density profiles are presented, and the occurrence of fluid flow leading to macrosegregation is linked to the solidification sequence of these alloys. This paper also mentions the possible us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Furthermore, experimental studies suggest that the existing experimental data of partition coefficients are insufficient for accurately predicting the alloy behavior, with regard to the promptness of forming macrosegregation defects. Using alloy 718, Aubertin et al [11] found an experimentally measured Nb partition coefficient of 0.35, while Knorovsky et al [14] reported experimental results for the Nb partition coefficient of approximately 0.5 for the same alloy. This indicates that a critical need exists to systematically investigate the partition coefficients by experimentation, for verification of the theoretical calculations.…”
Section: B Partition Coefficientmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, experimental studies suggest that the existing experimental data of partition coefficients are insufficient for accurately predicting the alloy behavior, with regard to the promptness of forming macrosegregation defects. Using alloy 718, Aubertin et al [11] found an experimentally measured Nb partition coefficient of 0.35, while Knorovsky et al [14] reported experimental results for the Nb partition coefficient of approximately 0.5 for the same alloy. This indicates that a critical need exists to systematically investigate the partition coefficients by experimentation, for verification of the theoretical calculations.…”
Section: B Partition Coefficientmentioning
confidence: 97%
“…[11,12] Because the change in the liquid density is induced by the redistribution of solute elements during solidification, the partition or distribution coefficients of the solute elements defined by Eq. [3] are very important metallurgical parameters for freckling prediction affecting the Rayleigh number:…”
Section: B Partition Coefficientmentioning
confidence: 99%
“…M6C has also been reported (3) in samples which have undergone longterm heat treatment, forming in small amounts at grain boundaries. Carbon is almost insoluble in the primary gamma phase of 718 and segregates strongly during solidification (4). As a result, although there are no carbides precipitated in the liquid above the liquidus temperature (1330C) (5) When the temperature falls to 1280C, corresponding to approximately 50% solidification (6,7,8), the carbon concentration in the remaining liquid rises to the point where the solubility product of NbC is exceeded and the precipitation of NbC therefore commences.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, although there are no carbides precipitated in the liquid above the liquidus temperature (1330C) (5) When the temperature falls to 1280C, corresponding to approximately 50% solidification (6,7,8), the carbon concentration in the remaining liquid rises to the point where the solubility product of NbC is exceeded and the precipitation of NbC therefore commences. This process is aided by the strong segregation of Nb, which leads to an Nb concentration of 10 wt% at the point of 50% solidification (4). The solubility product of NbC has been computed (5) at this temperature on the basis of the assumed and measured segregation coefficients of Nb and C. The carbide precipitation continues during the remaining solidification.…”
Section: Introductionmentioning
confidence: 99%
“…Once solidified, there is still the potential for the movement of atoms via diffusion however the relatively large size of Nb makes this process slow, meaning that little to no solid solute redistribution of Nb, to move towards an equilibrium distribution, occurs, following the Scheil equation (Auburtin et al, 1997;DuPont et al, 2009). This process of segregation results in the structures observed in Figure 40 and Figure 41 which show the solidification sub grains (SSG).…”
Section: Chemical Segregationmentioning
confidence: 99%